Heterogeneity in the Epigenetic Landscape of Murine Testis-Specific Histone Variants TH2A and TH2B Sharing the Same Bi-Directional Promoter - Singh, Isha; Parte, Priyanka (Frontiers in Cell and Developmental Biology, 2021)
Testis specific histone variants are crucial to promote open chromatin structure to enable nucleosome disassembly in the final stages of spermiogenesis. However, even after histone replacement, mature sperm retain a proportion of these variants, function of which is unknown. The present study aimed to understand the functional relevance of the retained H2B and H2A variants, TH2B and TH2A. Whilst no literature is available on the phenotype of TH2A knockouts, TH2B/TH2A double knock-out male mice are reported to be infertile. In this study, ChIP-seq analysis was done for TH2B and TH2A to understand the epigenomics of the retained TH2B and TH2A, using murine caudal sperm. Distribution across genomic partitions revealed ~35% of the TH2B peaks within ±5kb of TSS whereas TH2A peaks distribution was sparse at TSS. Gene Ontology revealed embryo development as the most significant term associated with TH2B. Also, based on genomic regions, TH2B was observed to be associated with spindle assembly and various meiosis-specific genes, which is an important finding as TH2A/TH2B DKO mice have been reported to have defective cohesin release. A comparison of mouse- and human TH2B linked chromatin revealed 26% overlap between murine- and human TH2B associated genes. This overlap included genes crucial for embryogenesis. Most importantly, heterogeneity in the epigenetic landscape of TH2A and TH2B was seen which is intriguing as TH2B and TH2A are well reported to be present in the same nucleosomes to promote open chromatin. Additionally, unlike TH2B, TH2A was enriched on the mitochondrial chromosome. TH2A was found to be associated with Nuclear insertion of Mitochondrial DNA sequences (NUMTs) in sperm. A comprehensive analysis of these observations indicates novel functions for the sperm retained TH2B and TH2A.